2010
DOI: 10.1016/j.jcrs.2009.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate visual function with different multifocal intraocular lens models

Abstract: Patients with bilateral multifocal aspheric IOLs with a lower add had better intermediate and distance near visual acuity than patients with bilateral multifocal spherical IOLs or bilateral aspheric IOLs with a higher add.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
95
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 22 publications
14
95
1
Order By: Relevance
“…In the present study, both corrected and uncorrected VA for far and near vision were comparable to those previously reported after implantation of earlier bifocal IOLs (18,26,27). This is consistent with findings in a recent comparative study by Mojzis et al (22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, both corrected and uncorrected VA for far and near vision were comparable to those previously reported after implantation of earlier bifocal IOLs (18,26,27). This is consistent with findings in a recent comparative study by Mojzis et al (22).…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, many studies have demonstrated that refractive (1-4), diffractive (5)(6)(7)(8)(9), and hybrid (10)(11)(12)(13)(14) IOLs provide good distance and near vision when implanted. However, the visual function at intermediate distance in patients with these bifocal IOLs has been shown to be somewhat poorer compared with that at far and near distances (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 96%
“…This multifocal IOL has the same symmetric biconvex design and anterior aspheric optic but a lower addition (add). Findings in previous studies [8][9][10][11][12][13][14][15] provide evidence that the C3.00 diopter (D) add version yields better intermediate vision and a more comfortable reading distance than the C4.00 D add version.The aim of this study was to determine in vivo whether the improvement in intermediate vision after bilateral implantation of the aspheric multifocal IOL ARTICLE with a C3.00 D add occurs at the expense of optical quality compared with that after bilateral implantation of the aspheric multifocal IOL with a C4.00 D add. To our knowledge, this is the first study to use in vivo analyses of optical quality parameters, such as the modulation transfer function (MTF) and point spread function (PSF) (expressed as the Strehl ratio), in patients with the C3.00 D add Acrysof Restor SN6AD1 IOL.…”
mentioning
confidence: 91%
“…In addition, the center-most region of the 3.6 mm area is larger than in the C4.00 D add version (0.856 mm versus 0.742 mm), creating bifocality from near to far and providing C3.00 D near add at the lens plane. [8][9][10][11][12][13][14][15] Immersion ultrasound biometry (Ocuscan RxP, Alcon Laboratories, Inc.) was performed in all cases by the same experienced examiner. All eyes were targeted for emmetropia.…”
mentioning
confidence: 99%
“…However, bifocals can impair visual detection of obstacles located on the floor or lower level because of impaired depth perception and contrast sensitivity [3]. This impairment is pronounced when potential hazards are viewed from intermediate distances (30-80 cm) [4], such as during stair navigation; therefore, bifocals are considered a fall risk factor in older adults that could lead to injury [3,[5][6]. Stair falls are responsible for 10 percent of fatal fall accidents [7].…”
Section: Introductionmentioning
confidence: 99%